MANAJEMEN STRATEGI PENERAPAN KEBIJAKAN KURIKULUM 2013 OLEH DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN KARAWANG - Annisa Ayu Rahmasari; Eka Yulyana; Kariena Febriantin (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2021)
This research is aimed to explain the management strategy of the Department of Education Youth and Sports in implementing policies curriculum 2013 at the school level of junior high school in the District Karawang, which focuses on : the formulation of strategies, implementation strategies, and evaluation of strategies for the success of the policy of curriculum 2013. Methods were used in the study is that the method qualitatively with the model descriptive. Data were collected through the study of literature, observation, and interviews. The informant came from the education office and the school which consisted of principals, teachers, and students who were selected purposively. The result of this study indicate that it is in stage formulation of a strategy, basic guidelines for the implementation of the policy of the curriculum in 2013 is planning the implementation of the curriculum in 2013, strengthening the source of the power main and supporting, strengthening learning at school, and strengthening and monitoring and evaluation. Forms of socialization that is done, namely in the form of training and mentoring. In stage implementation strategy, long-term and short-term has been appropriate and in support with the availability of facilities and infrastructure that support and increase the quality of labor educator for the success of the implementation of the policy of curriculum 2013. SMP N 5 Karawang Barat become one of the pilot project of the implementation of the policy curriculum 2013. Outcome implementation of policies curriculum in 2013 can be seen on a number of quality graduates and the percentage of graduation at students of SMP N 5 Karawang Barat. In the phase of evaluation of the strategy the department has been able to overcome the obstacles that exist by way of involving teachers in activities of training, the discipline of the personnel both teachers and participants of learners more enhanced, facilities and infrastructure that is equipped. Keywords: Strategy Management, Policy Implementation, Curriculum 2013 .